1987
DOI: 10.1161/01.cir.76.4.850
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ultrasonic tissue characterization: backscatter power, endocardial wall motion, and their phase relationship for normal, ischemic, and infarcted myocardium.

Abstract: To understand the possible differences in reflected ultrasonic energy from normal, ischemic, and infarcted myocardium, we studied 20 open-chest dogs with a commercially available two-dimensional ultrasonic scanner. Echocardiographic radiofrequency images of anterior myocardium were obtained serially during complete coronary occlusion for 2 hr (n = 15) or 5 hr (n = 10), or after temporary coronary clamping for 15 min with release for 1 hr (n = 5). We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 46 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…This hypothesis is supported by several experimental studies, [18][19][20][21][22] wherein this parameter has been demonstrated to decrease with myocardial ischemia19,22 and infarction.21,22 As opposed to measurement of absolute IB, the variation in IB in humans is obtainable with a current system because it does not require any calibration of ultrasound signals and subsequent standardization among subjects. Thus, cardiac cycle-dependent variation of IB can be used to assess alterations in the acoustic properties of the myocardium even in humans.…”
Section: Discussionmentioning
confidence: 78%
“…This hypothesis is supported by several experimental studies, [18][19][20][21][22] wherein this parameter has been demonstrated to decrease with myocardial ischemia19,22 and infarction.21,22 As opposed to measurement of absolute IB, the variation in IB in humans is obtainable with a current system because it does not require any calibration of ultrasound signals and subsequent standardization among subjects. Thus, cardiac cycle-dependent variation of IB can be used to assess alterations in the acoustic properties of the myocardium even in humans.…”
Section: Discussionmentioning
confidence: 78%
“…Certain statistical signal features have enabled investigators to distinguish among different types of tissue structure (25,26). For example, normal versus infarcted myocardium can be distinguished by integrated backscatter measurements (27) as well as their particular probability distribution functions (28). However, clinical utility has been limited because of several inherent problems, such as low frequency in order to gain penetration, motion artifacts caused by myocardial contraction and intervening tissue structure, and tissue anisotropy.…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Certain statistical signal features have enabled investigators to distinguish between different types of tissue structure.34,35 For example, normal vs. infarcted myocardium can be distinguished by integrated backscatter measurements,36 as well as their particular probability distribution functions. 37 However, clinical utility has been limited because of several inherent problems. The use of low frequency to gain penetration has limited resolving capabilities of the tissue characterization techniques.…”
Section: Clinical Applicationsmentioning
confidence: 99%